Public debt, GDP and the Sovereign Debt Laffer curve: a country-specific analysis for the Euro Area - Bhimjee, D. (2020)
This article analyses the non-linear association between public debt and GDP for the Euro Area since the introduction of the euro. It draws on a theoretical concept – the sovereign debt Laffer curve - previously proposed in literature. Our empirical research design contemplates: (i) estimating a public debt Laffer curve for each Euro Area country; (ii) computing country thresholds from the estimated Laffer curves, i.e., the points beyond which further increases in public debt have damaging effects on output; (iii) analyzing the deviations of the current debt position of each country relative to the respective optimal threshold. We conclude that certain Member States have already gone beyond their optimal thresholds, meaning public debt is already limiting output growth. Our contribution to the field consists in the estimation of country-specific thresholds for each Euro Area Member State. To do this we ran a separate quadratic regression for each country, instead of aggregating multiple countries in a single estimation.